2005
DOI: 10.1167/iovs.04-1133
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Course of Patients with Glaucoma with the E50K Mutation in the Optineurin Gene

Abstract: In this study, subjects with glaucoma who had the OPTN E50K mutation were found to have NTG that appeared to be more severe than that in a control group of subjects with NTG without this mutation. The findings emphasize the importance of early detection and treatment of glaucoma in such individuals, to minimize visual loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(87 citation statements)
references
References 41 publications
5
76
0
1
Order By: Relevance
“…Therefore, it is less likely that the younger patients were detected earlier in the progress of the disease than the older ones. Aung et al 30 reported the mutation of optineurin gene is associated with the early onset (mean age of 40.8 years), more severe form of NTG. This result also could be interpreted as the early onset NTG has a distinct genetic pathogenesis from the late onset NTG.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is less likely that the younger patients were detected earlier in the progress of the disease than the older ones. Aung et al 30 reported the mutation of optineurin gene is associated with the early onset (mean age of 40.8 years), more severe form of NTG. This result also could be interpreted as the early onset NTG has a distinct genetic pathogenesis from the late onset NTG.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NPG subjects who had E50K mutation were reported clinically to suffer glaucomatous defects more severe than those without this mutation. 46 It is also of note that PROSITE analysis 47 indicates that introduction of Glu 50 3 Lys mutation results in no particular changes either in the structure or the conformation of OPTN (data not shown). The E50K mutation may conceivably affect the protein activity or property by other mechanisms such as posttranslational phosphorylation.…”
Section: Studies Of Optineurin a Glaucoma Gene 1985mentioning
confidence: 91%
“…24,25 The Glu50Lys (E50K) mutation, found in Caucasian and Hispanic populations, 25 seems to be associated with a more progressive and severe disease in patients with normal tension glaucoma. 26 The human optineurin gene codes for a 577-amino acid protein that contains multiple coiled-coil domains and a C-terminal zinc finger. 27,28 The optineurin protein from different species has high amino acid homology.…”
mentioning
confidence: 99%